2001
DOI: 10.1002/bin.79
|View full text |Cite
|
Sign up to set email alerts
|

Functional assessment and treatment of pica: a single‐case experiment

Abstract: The pica of a 6-year-old girl diagnosed with autism was initially shown to persist in the absence of socially mediated consequences. In an attempt to provide a competing source of oral stimulation, we used a stimulus preference assessment to identify food items that were subsequently presented noncontingently. However, the noncontingent schedule could not be thinned to a practical variation while still maintaining reductions in pica. A subsequent multielement evaluation of response blocking and verbal repriman… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…Although pica (the ingestion of nonnutritive substances) represents one form of SIB that is often maintained by its own consequences, response blocking as an intervention for pica has produced mixed results. For example, Rapp, Dozier, and Carr (2001) reported that response blocking (when used independently) did not reduce pica to clinically acceptable levels and produced aggression as an unwanted side effect. By contrast, LeBlanc, Piazza, and Krug (1997) found that response blocking was just as effective as restraint in preventing a young girl's pica and was associated with less therapist effort and fewer negative vocalizations.…”
Section: ____________________________________________________________mentioning
confidence: 99%
“…Although pica (the ingestion of nonnutritive substances) represents one form of SIB that is often maintained by its own consequences, response blocking as an intervention for pica has produced mixed results. For example, Rapp, Dozier, and Carr (2001) reported that response blocking (when used independently) did not reduce pica to clinically acceptable levels and produced aggression as an unwanted side effect. By contrast, LeBlanc, Piazza, and Krug (1997) found that response blocking was just as effective as restraint in preventing a young girl's pica and was associated with less therapist effort and fewer negative vocalizations.…”
Section: ____________________________________________________________mentioning
confidence: 99%
“…VRs were used in 11 studies and included verbal utterances informing the youth when their behaviour is undesirable or unacceptable. These utterances ranged from direct instructions (e.g., “not in mouth”; p. 113, Rapp et al, 2001), to shouting “no” at the child (e.g., p. 137, Bucher et al, 1976). Of these 11, five studies that included VR as part of a treatment package effectively reduced pica to near‐zero rates (Bucher et al, 1976; Johnson et al, 1994; Kalfus & Burk, 1989; Piazza et al, 1998, 1996).…”
Section: Resultsmentioning
confidence: 99%
“…For example, youth can be rewarded with preferred food or toys when they do not engage in pica behaviours (Sinha & Mallick, 2010). Three out of four studies that included CR were effective in lowering pica to near‐zero rates (Kalfus & Burk, 1989; Rapp, Dozier, & Carr, 2001; Sinha & Mallick, 2010). In two of the effective treatments, CR was included as part of a combination treatment with punishment procedures (Kalfus & Burk, 1989; Rapp et al, 2001) and response interruption (Rapp et al, 2001).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Attempts to reduce or eliminate pica have involved a range of treatments, from drug (Ginsberg, ) and vitamin therapies (Pace & Toyer, ) to behavioral therapies (Foxx & Martin, ; Goh, Iwata, & Kahng, ). In the behavioral assessment of pica, most researchers have found that the behavior is partially if not completely maintained by automatic reinforcement (Ing, Roane, & Veenstra, ; Mace & Knight, ; Piazza, Hanley, & Fisher, ; Piazza et al, ; Rapp, Dozier, & Carr, ). It is possible that because automatically reinforced behavior is difficult to extinguish and alternative reinforcers would have to compete with the automatic reinforcement produced by the pica itself, some reinforcement procedures alone have not been effective at reducing pica (Finney, Russo, & Cataldo, ; Fisher et al, ; Hagopian, Gonzalaz, Rivet, Triggs, & Clark, ).…”
Section: Introductionmentioning
confidence: 99%